Indole-Acrylonitrile Derivatives as Potential Antitumor and Antimicrobial Agents-Synthesis, In Vitro and In Silico Studies - Anita Kornicka; Karol Gzella; Katarzyna Garbacz; Małgorzata Jarosiewicz; Maria Gdaniec; Joanna Fedorowicz; Łukasz Balewski; Jakub Kokoszka; Anna Ordyszewska (MDPI AG, 2023)
A series of 2-(1H-indol-2-yl)-3-acrylonitrile derivatives, 2a-x, 3, 4a-b, 5a-d, 6a-b, and 7, were synthesized as potential antitumor and antimicrobial agents. The structures of the prepared compounds were evaluated based on elemental analysis, IR, 1H- and 13NMR, as well as MS spectra. X-ray crystal analysis of the representative 2-(1H-indol-2-yl)-3-acrylonitrile 2l showed that the acrylonitrile double bond was Z-configured. All compounds were screened at the National Cancer Institute (USA) for their activities against a panel of approximately 60 human tumor cell lines and the relationship between structure and in vitro antitumor activity is discussed. Compounds of interest 2l and 5a-d showed significant growth inhibition potency against various tumor cell lines with the mean midpoint GI50 values of all tests in the range of 0.38-7.91 μM. The prominent compound with remarkable activity (GI50 = 0.0244-5.06 μM) and high potency (TGI = 0.0866-0.938 μM) against some cell lines of leukemia (HL-60(TB)), non-small cell lung cancer (NCI-H522), colon cancer (COLO 205), CNS cancer (SF-539, SNB-75), ovarian cancer ((OVCAR-3), renal cancer (A498, RXF 393), and breast cancer (MDA-MB-468) was 3-[4-(dimethylamino)phenyl]-2-(1-methyl-1H-indol-2-yl)acrylonitrile (5c). Moreover, the selected 2-(1H-indol-2-yl)-3-acrylonitriles 2a-c and 2e-x were evaluated for their antibacterial and antifungal activities against Gram-positive and Gram-negative pathogens as well as Candida albicans. Among them, 2-(1H-indol-2-yl)-3-(1H-pyrrol-2-yl)acrylonitrile (2x) showed the most potent antimicrobial activity and therefore it can be considered as a lead structure for further development of antimicrobial agents. Finally, molecular docking studies as well as drug-likeness and ADME profile prediction were carried out.